Managing Crisis to Recovery: The Road Ahead for India - Srivastava, Divya; Srivastava, Shashi (Indian Journal of Finance, 2010)
According to Prof. James Van Horne of Stanford University, credit crisis in US, often caused or accompanied by real estate collapses, occurred on an average once every 14 years from 1800 to 1970s and once every 8 years since 1970. During the panic of 1819, real estate speculation involved farmland on the Ohio frontier. In the panic of 1837, there was a real estate bubble along the Mississipi. The panic of 1873 and 1893 involved investments in land near rail lines. The crash of 1929 was preceded by the bursting of real estate bubbles in Florida&Southern California. After 9/11, American people were encouraged to spend in the spirit of patriotism to help restart the failing economy. To fuel that spending, in the extraordinary political and psychological climate of that time, U.S. policy makers actively encouraged levels of borrowing and lending that would never have been allowed otherwise. Federal reserve cut interest rate to 1%, the financial services industry sensed that a lot of money could be made and went over-vigorously in real estate, seemingly unaware that low interest rate could be disguising larger risks. Commercial banks and investment banks lent for house purchases and consumer loans to borrowers who were not really equipped to repay. The easy lending pushed up housing prices, which then went up still higher, when speculators bought houses on the expedition of further price increases. The price rose significantly because of easier access to funds/loans as also historically low interest rate, looser lending, low appraisal standards and documentation. When the easy lending initially slowed and eventually stopped during 2006-07, housing prices peaked. However, once interest rates began to rise and housing prices started to drop moderately, refinancing became more difficult.Defaults and foreclosure activity increased dramatically as easy initial terms expired, home prices failed to go up as anticipated, and interest rates reset higher and this triggered a global financial crisis through 2007 and 2008. In the world economic forum annual meeting in Dalian, a Chinese participant remarked, "The teachers have made big mistakes." (Martin Wolf, Financial Times, Sep 14’ 09).